The millionaires - Meltzer, Brad (New York : Warner Books, 2002)
Brothers Charlie and Oliver Caruso work at the exclusive bank Greene and Greene but when the brothers find out that a colleague has been sabotaging Oliver's career plans they conspire to steel $3 million from a deceased client's account. With the Secret Service closing in and a friend found dead the brothers must escape to Florida to try and clear their names.
Keywords: Embezzlement -- Fiction; Private banks -- Fiction; Banks and banking -- Fiction